Anies Baswedan's Leadership in Literacy Campaign Minis-ter of Education and Culture (2014-2016) - Siti Andriana; Hasnah Faizah (International Journal of Studies in International Education, 2025)
This article analyzes Anies Baswedan's leadership in driving the national literacy campaign during his tenure as Indonesia's Minister of Education and culture from 2014 to 2016. This study uses a qualitative approach with a case study method, with data sources in the form of policy documents, program reports, and literature related to leadership and literacy. The results showed that the transformational leadership style implemented by Anies Baswedan was effective in building a common vision and motivating various stakeholders to actively participate in national literacy programs, especially the School Literacy Movement (GLS). The leadership is able to foster a culture of sustainable literacy in schools and communities, although still faced with challenges in the form of limited resources and access gaps. Overall, Anies Baswedan's leadership contributed significantly to improving the quality of education and strengthening national literacy as an important foundation to face the challenges of 21st Century Education. Keywords: transformational leadership, Literacy Campaign, School Literacy Movement, Anies Baswedan, literacy culture, education policy, 21st Century Education.